Information Asymmetry in Business-to-Business Negotiations: A Game Theoretical Approach to Support Purchasing Decisions with Suppliers - Frank Bodendorf; Barbara Hollweck; Jörg Franke (Group Decision and Negotiation, 2022)
The digital transformation confronts purchasing and supply management (PSM) with numerous new challenges, such as digital procurement objects and the information asymmetry between buyers and suppliers. Existing approaches contributing to PSM research (e. g., the selection of suppliers or the calculation of equilibrium prices) have in common that information regarding suppliers (e. g., production costs) must be well-known. However, this information is rarely accessible to purchasers due to the existing information asymmetry. This problem is addressed by a game-theoretical model based on a Stackelberg game to assist PSM in dealing with the information advantage of software suppliers. The applicability in practice is evaluated by a real-world case study from the automotive industry. The results show that the presented model can support decision-making in purchasing by a qualitative analysis of profit scenarios for different negotiation strategies. The model contributes to dismantling the information asymmetry and provides a basis for determining negotiation prices, also for digital procurement objects. This research motivates both supply and purchase managers to jointly optimize their product costs and thus increase their competitiveness on the market.
Keywords: 650; Game theory; Information asymmetry; Decision support; Negotiation; Supply management; Cost management